Efficacy of low-dose Topiramate in Migraine Prophylaxis - Momen Khan, Muhammad Abdul; Ali Miah, Mohammad Bahadur; Shahidullah, Md; Islam, Md Rafiqul; Day, Subash Kanti; Ferdous, Jannatul; Hossain, Md Amir (Bangladesh Journal of Neuroscience, 2015)
Background: Anticonvulsants are now commonly used for migraine prophylaxis, among them topiramate, one of the newer anticonvulsants, recently has been demonstrated to be effective as mono-therapy for migraine prophylaxis. Objectives: To observe the efficacy and safety of low dose topiramate in migraine prophylaxis. Methods: This prospective trial was carried out in the Out Patient Department (OPD) & Headache Clinic, Department of Neurology, Bangabandhu Sheikh Mujib Medical University, Dhaka. Total 60 patients around the age range of 18 to 50 years diagnosed as migraine (with aura or without aura) according to ICHD-3 criteria, were recruited as the study population. Total 60 patients were administered by Tab.Topiramate 50 mg/ day. Out of them, total 47 patients had completed the study due to drop out of 13 patients. During trial, three follow up visits were taken, 1st follow up after 4 weeks of baseline information (Before starting prophylactic medication), 2nd follow up after 4 weeks of treatment, 3rd follow up after 8 weeks of treatment. Efficacy of treatment was measured by headache frequency, duration and severity as measured by the VAS. Effectiveness was assessed by comparing baseline & on-treatment migraine status. Results: The mean (SD) age of patients were found 29.72 (9.58) years. Female sex was predominant. The mean (SD) value of frequency of migraine at baseline level with 1st and 2nd follow up were statistically significant [Baseline 9.28 (2.39) vs. 1st FU 7.55 (3.07), p=0.001; Baseline 9.28 (2.39) vs. 2nd FU 4.72 (2.80), p<0.001]. Duration of each episode of migraine ,comparing the mean (SD) value of duration of migraine of baseline level with 1st and 2nd follow up were statistically significant [Baseline 10.85 (5.26) vs. 1st FU 8.06 (4.11) hr, p<0.001; Baseline 10.85 (5.26) vs. 2nd FU 5.53 (2.98) hr, p<0.001]. According to severity of migraine based on VAS in base line period all patients had experienced moderate & severe headache but in 1st follow up, few patients had experienced mild headache from moderate headache, few patients had experienced moderate headache from severe headache & in 2nd follow up, patients had better condition and had experienced mild and moderate headache, no patient had experienced severe headache. In this study, 23.4% patients developed adverse effects. Among the adverse effects, 8.5% develop dizziness, 6.3% drowsiness, 4.2% anorexia & blurring of vision. Conclusion: The present study suggest that low dose topiramate are effective for migraine prophylaxis in reduction of frequency, severity and duration of migraine headache . Bangladesh Journal of Neuroscience 2015; Vol. 31 (2): 70-75